Mitigating the impact of mercury on rural people by providing scenarios on alternative income through corn farming improvement - Sirajuddin, Zulham; Pateda, Sri Manovita; Baruwadi, Mahludin; Tahir, Nur Safitri (Asian Journal of Agriculture and Rural Development, 2024)
The purpose of this research is to examine several scenarios in corn farming, which can be an alternative income for rural communities involved in ASGM. The artisanal and small-scale gold mining (ASGM) activities in Tulabolo, Gorontalo, have negatively impacted the local community’s health due to mercury amalgamation pollution. Therefore, alternative scenarios are needed to attract the interest of the mining community to return to farming. Interviews were conducted with 26 farmers engaged in both mining and corn farming activities using an interview guide to assess their current cultivation behaviour and income related to ASGM, and other relevant informants. The data collected indicated that farmers earn significantly higher income from mining than from corn farming. Therefore, to incentivize farmers to shift their focus to corn farming, this study analyse several scenarios; increasing the land area per individual to a minimum of 2.2 hectares, raising the selling price of corn kernel to a minimum of IDR 9,203 per kg, and increasing productivity to a minimum of 2,709 kg/Ha through improved farming techniques. Implementing the third scenario is recommended to enhance earnings while reducing the negative impacts of ASGM on both health and the environment.